When designer meets local culture: The promising learning trajectory on the surface area of polyhedron - Adha, Idul; Zulkardi; Putri, Ratu Ilma Indra; Somakim (Journal on Mathematics Education, 2024)
Polyhedrons present a challenging topic in elementary geometry education. The Indonesian Realistic Mathematics Education (IRME) approach, when contextualized within the Bukit Sulap tourism area, offers a promising solution to this challenge. This study aims to design a learning trajectory for teaching the surface area of polyhedron using IRME in the context of Bukit Sulap tourism. Employing a research design with a validation study type, the study was conducted in three phases: preparation and design, experimental teaching, and retrospective analysis. The participants were 27 elementary school students from Lubuklinggau City, Indonesia. Data collection instruments included surface area problem-solving worksheets, video recordings of in-depth learning interviews, field notes, and observation sheets. The findings suggest that the Bukit Sulap tourism context significantly enhanced students' understanding of surface area problems, specifically those involving combinations of cuboids and cubes. Additionally, IRME effectively facilitated students' comprehension of abstract mathematical concepts, particularly the surface area formulas for cubes and cuboids. The study concludes that using the Bukit Sulap tourism park context as a starting point for teaching the surface area of polyhedron aligns well with the principles of IRME.